2019
DOI: 10.1016/j.pmedr.2019.100961
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Prevention Program attendance is associated with improved patient activation: Results from the Prediabetes Informed Decisions and Education (PRIDE) study

Abstract: The Diabetes Prevention Program (DPP) is a 12-month behavior change program designed to increase physical activity and improve dietary patterns among patients at risk for Type 2 diabetes, in order to facilitate modest weight loss and improve cardio-metabolic profiles. It is unknown whether baseline patient activation is related to increased DPP uptake, and whether DPP attendance leads to subsequent improvement in patient activation. We analyzed data from 352 adult participants in the Prediabetes Informed Decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
3
12
0
Order By: Relevance
“…Moreover, we demonstrated the predictive role of the individual's general health engagement attitude in the intention to vaccinate against COVID-19. Our results corroborate the relevance of studying the general individual's psychological attitude towards their health promotion and self-management-namely, health engagement-as a relevant factor impacting on preventive behaviors [15,[32][33][34]. Furthermore, these data corroborate the value of extending the current debate about patient engagement to the specific scope of vaccine intention [35].…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, we demonstrated the predictive role of the individual's general health engagement attitude in the intention to vaccinate against COVID-19. Our results corroborate the relevance of studying the general individual's psychological attitude towards their health promotion and self-management-namely, health engagement-as a relevant factor impacting on preventive behaviors [15,[32][33][34]. Furthermore, these data corroborate the value of extending the current debate about patient engagement to the specific scope of vaccine intention [35].…”
Section: Discussionsupporting
confidence: 83%
“…Given that participants who were enrolled in the GLB program were invited to participate in the study, this appears to be a representative sample of individuals interested in this weight‐management program. Furthermore, the NOW trial study population is similar to other reported GLB study populations (40‐43).…”
Section: Discussionsupporting
confidence: 72%
“…Translation of this program to real-world settings and delivery to medically underserved populations and those at increased risk, however, may yield less effective outcomes. In alignment with previous studies ( 14 , 17 , 28 ), our findings highlight that program attendance and engaging in the recommended amounts of physical activity are key drivers of program effectiveness. Not all participants, however, are able to meet attendance and physical activity recommendations.…”
Section: Discussionsupporting
confidence: 89%